Propuesta de Metodología para la Gestión de Proyectos de Alianzas Estratégicas en la División Banda Ancha del Sector Telecomunicaciones del ICE a fin de brindar Soluciones de Tercerización a Clientes Empresariales - Santamaría-Sandoval, José Roberto; Jiménez-Aguirre, María (Instituto Tecnológico de Costa Rica, 2013)
Currently, the Instituto Costarricense de Electricidad (ICE) offers a range of customized solutions for enterprise customers-level Information Technology (IT), and its main drawback response time for delivery of these. Having strategic alliances collaborate in resolving the situation. This research is to propose a methodology to manage projects of strategic alliances at Broadband Division Telecommunications Sector ICE, for which activities were performed as: 1. A diagnosis of the current situation by providing a gap analysis. 2. Making the proposed methodology with their techniques and tools to level knowledge areas defined as essential for this research. They also do a proposed implementation plan and value added elements such as: 1. Operational Process for the operational management of the alliance with their roles and functions. 2. Dictionaries and complementary tools and user-friendly application for project managers.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2013.
Keywords: Gestión de proyectos; Sistemas de información; Contrataciones; Diagnóstico; Estrategia